2002
DOI: 10.1046/j.1523-1755.2002.00553.x
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of PPARalpha and its coactivator PGC-1 in cisplatin-induced acute renal failure

Abstract: These results demonstrate that cisplatin deactivates PPARalpha by reducing its DNA binding activity and the availability of its tissue specific coactivator PGC-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
62
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(72 citation statements)
references
References 30 publications
9
62
1
Order By: Relevance
“…27 Several studies indicate that the AMPK, PPARa, and PGC1a pathways are important in fibrosis development. 29,[48][49][50][51] Data from the Duffield group suggest that microRNA 21 is an important upstream regulator of the pathway. 52 In conclusion, this study showed that selective deletion of Lkb1 in the kidney induced severe injury over time, characterized by dilated tubules and interstitial fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…27 Several studies indicate that the AMPK, PPARa, and PGC1a pathways are important in fibrosis development. 29,[48][49][50][51] Data from the Duffield group suggest that microRNA 21 is an important upstream regulator of the pathway. 52 In conclusion, this study showed that selective deletion of Lkb1 in the kidney induced severe injury over time, characterized by dilated tubules and interstitial fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to DNA damage, cisplatin inhibits fatty acid oxidation that is the main source of energy for the proximal tubule through reduction in PPAR-a mediated expression of genes involved in cellular fatty acid utilization. [21][22][23] Cisplatin also inhibits the mitochondrial complexes I to IV of the respiratory chain and induces decrease in intracellular ATP levels. 24 Creatine can prevent cell damage with two possible mechanisms: stabilization of cellular membranes and maintenance of ATP.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, mitochondrial number is decreased after oxidative stress observed in models of ischemiareperfusion injury or from the cumulative oxidative stress associated with aging (Lemasters, 2005;Rasbach and Schnellmann, 2007b). Several disease models or toxicants decrease the expression of PGC-1␣ and are associated with impaired mitochondrial biogenesis (Portilla et al, 2002;Priault et al, 2005). Therefore, disease states or injury models associated with mitochondrial dysfunction and/or impaired biogenesis of mitochondria is therefore attractive targets for therapeutics aimed at stimulating the mitochondrial biogenesis pathway.…”
Section: Discussionmentioning
confidence: 99%